Harnessing Inflammation Resolution in Arthritis: Current Understanding of Specialized Pro-resolving Lipid Mediators’ Contribution to Arthritis Physiopathology and Future Perspectives - Zaninelli, Tiago H.; Fattori, Victor; Verri, Waldiceu A. (Frontiers in Physiology, 2021)
The concept behind the resolution of inflammation has changed in the past decades from a passive to an active process, which reflects in novel avenues to understand and control inflammation-driven diseases. The time-dependent and active process of resolution phase is orchestrated by the endogenous biosynthesis of specialized pro-resolving lipid mediators (SPMs). Inflammation and its resolution are two forces in rheumatic diseases that affect millions of people worldwide with pain as the most common experienced symptom. The pathophysiological role of SPMs in arthritis has been demonstrated in pre-clinical and clinical studies (no clinical trials yet), which highlight their active orchestration of disease control. The endogenous roles of SPMs also give rise to the opportunity of envisaging these molecules as novel candidates to improve the life quality of rhematic diseases patients. Herein, we discuss the current understanding of SPMs endogenous roles in arthritis as pro-resolutive, protective, and immunoresolvent lipids.